Fault current test of a bifilar Bi-2212 bulk coil - Baldan, Carlos Alberto [UNESP]; Shigue, Carlos Y.; Ruppert Filho, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2008)
A bifilar Bi-2212 bulk coil with parallel shunt resistor was tested under fault current condition using a 3 MVA single-phase transformer in a 220 V-60 Hz line achieving fault current peak of 8 kA. The fault current tests are performed from steady state peak current of 200 A by applying controlled short circuits up to 8 kA varying the time period from one to six cycles. The test results show the function of the shunt resistor providing homogeneous quench behavior of the HTS coil besides its intrinsic stabilizing role. The limiting current ratio achieves a factor 4.2 during 5 cycles without any degradation.
Keywords: Bi-2212 bulk coil; HTS bifilar coil; HTS coils; superconducting fault current limiter